PROGRAM KEBERSYUKURAN UNTUK MENGATASIGEJALA GANGGUAN STRES PASCA TRAUMA PADA REMAJA PENYINTAS ERUPSI MERAPI - , DHIAN PUSPITASARI, Prof. Dr. Sofia Retnowati ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Natural disasters are common in Indonesia. One of the biggest natural disasters in 2010 was the eruption of Merapi. Based on research Hidayat (2010), victims of the eruption of Merapi in 2010 showed high anxiety, post-traumatic stress disorder, to depression symptoms. According to Parkinson (1993) posttraumatic stress disorder is a characteristic symptom of psychological distress followed about an event that is beyond the scope of experience of people in general. Based on the research Kashdan, Uswatte, and Julian (2006), a person who suffered post-traumatic stress disorder have low levels of gratitude. This study aimed to test whether the gratitude program can overcome post-traumatic stress disorder symptoms in adolescent survivors of the eruption of Merapi. The hypothesis of this research is the gratitude programcan overcome posttraumatic stress disorder symptoms in adolescent survivors of the eruption of Merapi. Subjects in this study were 24 male and female students of SMP Negeri 2 Cangkringan who is survivors of the Merapi eruption. Early adolescent, male and female. Willing to follow the gratitude program. Scale used in this study is a modification of the Child PTSD Symptom Scale scale (CPSS) developed by Foa, Johnson, Feeny, and Treadwell (2001). To test the hypothesis using a paired sample test and the independent sample test. Test results using a paired two-sample Wilcoxon signed rank (nonparametric), the value of Z = -0,801 with a significance level of p = 0,423 (p>0,05). Furthermore, based on two independent samples test at posttest using the Mann Whitney U test, Z = -0,434 with a significance level of p = 0,664 (p> 0,05). These results indicate that there is no significant change in symptom scores posttraumatic stress disorder. Thus, the research hypothesis was rejected.